Suppression of Rayleigh-Taylor instabilities in Z-pinches; Technical Physics Letters; Vol. 41, iss. 6 - Zhigalin A. S. Aleksandr Sergeevich; Rousskikh A. G. Alexander G.; Baksht R. B. Rina B.; Chaikovsky S. A.; Labetskaya N. A. Nataljya Anatoljevna; Oreshkin V. I. Vladimir Ivanovich (2015, 2015)
Title screen